The quadratic formula is given by th following formula:
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
where a, b and c are the coefficients of the quadratic equation. In this case, you have:
a = 6
b = 9
c = -22
replace the previous values into the quadratic formula and simplify:
![\begin{gathered} x=\frac{-9\pm\sqrt[]{(9)^2-4(6)(-22)}}{2(6)} \\ x=\frac{-9\pm\sqrt[]{609}}{12} \\ x_1\approx1.31 \\ x_2\approx-2.81 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3fqobp8ewi28tpcc7ko6du7jb46ajsppr7.png)
Hence, the solutions for the given equation are 1.31 and -2.81